EDUCATIONAL QUALITY MANAGEMENT IN INTEGRATED ISLAMIC SCHOOLS (The Role of Stakeholders in Improving the Quality of Edu) - Al Husaini, Muhammad; Siti Patimah; Andi Warisno; Nurul Hidayati Murtafiah (Cakrawala Pedagogik, 2024)
Education is a shared responsibility. Stakeholder involvement is very important in improving the quality of education. Stakeholders have different roles and responsibilities in realizing educational goals. Building effective partnerships and collaboration between stakeholders is the key to improving the quality of education. This article discusses the role of stakeholders in improving the quality of education based on analysis of data and facts, as well as quotes from experts' opinions. Several suggestions are also presented for increasing the role of stakeholders in education. In conclusion, by understanding the role of stakeholders and implementing appropriate strategies, schools can utilize existing potential and resources to improve the quality of education in a sustainable manner.